On the magnetic, mechanical and rheological properties of rubber-nickel nanocomposites - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Polymer Bulletin, 2010)
Rubber-nickel nanocomposites were synthesized by incorporating freshly prepared nanometric nickel particles in two different matrices namely natural rubber and neoprene rubber according to specific recipes for various loadings of nano nickel and the cure characteristics of these composites were evaluated. The maximum torque values register an increase with the increase in loading of nickel in both composites and this is attributed to the non-interacting nature of nickel nanoparticles with rubber matrices. The cure time of natural rubber composites decreases with increase in the content of nickel, and in neoprene rubber cure, time increases with increase in filler content. In natural rubber, the curing reaction seems to be activated by the presence of nickel particles. The magnetization studies of the composites reveal that the magnetic properties of nickel are retained in the composite samples. The elastic modulus of natural rubber and neoprene rubber are largely improved by the incorporation of nickel particles.
Keywords: Cure characteristics; Elastic modulus; magnetic properties; Nanocomposites